PROJECT ACTIVITY OF STUDENTS IN PHYSICS LESSONS - ONE OF THE DIRECTIONS OF DEVELOPMENT OF MODERN EDUCATION - O.M. Holodenko (Academy of Cognitive and Natural Sciences, 2010)
The question of introduction of innovative technologies of studies is examined in the article - important factor of organization and development of society. One of types of innovative technologies there is a method of projects, which allows to decide the various tasks of creative development of students.